Ministry of Petroleum and Mineral Resources Decree No. 1682 of the year 2021 = وزارة البترول والثروة المعدنية قرار رقم 1682 لسنة 2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic